2009
DOI: 10.1021/tx900114v
|View full text |Cite
|
Sign up to set email alerts
|

Spin Trapping and Cytoprotective Properties of Fluorinated Amphiphilic Carrier Conjugates of Cyclic versus Linear Nitrones

Abstract: Nitrone spin traps have been employed as pharmacological agent against neurodegenerative diseases and ischemia-reperfusion induced injury. The structure-activity relationship was explored for the two types of nitrones, i.e., cyclic (DMPO) and linear (PBN), which are conjugated to a fluorinated amphiphilic carrier (FAC) for their cytoprotective properties against hydrogen peroxide (H 2 O 2 ), 3-morpholinosynonimine hydrochloride (SIN-1) and 4-hydroxynonenal (HNE) induced cell death on bovine aortic endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 82 publications
2
43
0
Order By: Relevance
“…Finally, after purification by aqueous size exclusion chromatography, the Zempl en de-O-acetylation procedure led to compounds 11 and 12. The amphiphilic nitrones 11 and 12, as well as their acetylated derivatives 9 and 10, were fully characterized by 1 H, 13 C, 19 F, DEPT, and HMQC NMR as well as mass spectrometry (ESIþ). The purity of 11 and 12 was confirmed by C18 reverse phase HPLC and was higher than 95% (see Supporting Information).…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, after purification by aqueous size exclusion chromatography, the Zempl en de-O-acetylation procedure led to compounds 11 and 12. The amphiphilic nitrones 11 and 12, as well as their acetylated derivatives 9 and 10, were fully characterized by 1 H, 13 C, 19 F, DEPT, and HMQC NMR as well as mass spectrometry (ESIþ). The purity of 11 and 12 was confirmed by C18 reverse phase HPLC and was higher than 95% (see Supporting Information).…”
Section: Chemistrymentioning
confidence: 99%
“…Calculated Electron Affinities, Ionization Potentials, and Charge Densities of the Nitronyl Atoms of13,12,11, and PBN at the…”
mentioning
confidence: 99%
“…These amino-acid drug conjugates were then used as prodrugs to treat cancer cells. Furthermore, the development of amino acid-antioxidant conjugates and amino acid-anti-angiogenic conjugates were also recently reported in the literature (Ortial et al 2006;Durand et al 2009;Contino-Pépin et al 2009). Hence, amino-acid derivatives are a promising avenue, which must be further exploited in the search for new drug candidates.…”
Section: Introductionmentioning
confidence: 91%
“…Indeed, it is reported that m-tyrosine is significantly more phytotoxic than its structural isomers o-and p-tyrosine (Bertin et al 2007). Furthermore, it is reported that phenolic compounds exhibiting antioxidant properties can contribute to the destruction of cancer cells (Durand et al 2009). The slightly greater activity observed for the m-tyrosine regioisomer might be explained by these factors being more important for the meta isomer compared to the ortho and para isomers.…”
Section: In Vitro Biological Activitymentioning
confidence: 99%
“…Previous studies show that nitrones can upregulate eNOS phosphorylation thereby reversing SIN-1-induced eNOS dysfunction, and have cytoprotective properties against SIN-1 induced peroxynitrite toxicity [16, 17]. Some nitrones can also induce endogenous antioxidant enzymes [18], inhibit NF-κB activation [19], as well as donate NO, thereby increasing NO bioavailability [20, 21].…”
Section: Introductionmentioning
confidence: 99%